Aleksandr Bogdanov and Lenin on “Things-In-Themselves” - Oittinen Vesa (Cultural Science)
Questions on the theory of cognition formed one of the focal points in the dispute between orthodox Russian Marxists and Aleksandr Bogdanov and his followers. Bogdanov was an adherent of Mach’s theory, which abandoned Kant’s concept of “things-in-themselves” (Ding an sich) outside the cognizing subject. According to Mach and Bogdanov, there is no need to duplicate human experience in appearances given in the senses and things behind these appearances. The orthodox Marxists, Lenin as well as Plekhanov, insisted that Kant’s concept of things-in-themselves should be retained, but in a modified form: the things-in-themselves do not form a limit to our knowledge, as Kant (allegedly) thought, but turn into “things-for-us” in the everyday processes of material and scientific production. Both solutions, the Machian and the orthodox Marxist, have their problems. In the Soviet era, Lenin was depicted as the winner of the dispute. But a closer examination of Bogdanov’s arguments shows that he actually found some weak points in Lenin’s conception. However, this does not mean that Lenin’s critique of Bogdanov as a subjectivist in his theory of cognition was groundless.